Interactive Digital Storybooks: A Personalized Approach To ‎English Learning In Indonesian Primary School - Ulya Himawati; Danang Mahendra; Laila Ngindana Zulfa; Gadis Herningtyasari; Santi Andriyani; Hamidaturrohmah; Yulia Septiviyana (Yayasan Darussalam Bengkulu, 2026)
Primary English education in Indonesia faces challenges in developing learning resources that meet individual student needs. To address this, the Merdeka Belajar policy promotes a tailored learning approach. This study evaluates the use of an Interactive English Story Book that integrates interactive elements, audio, and visuals for fourth-grade students learning English. The evaluation was conducted by the researcher and the English teacher through classroom observations, interviews, and questionnaires over a three-week period, involving a small pilot sample of thirteen students aged nine to ten at Bina Putra School. The measured aspects included the domains of engagement (assessed by visual focus and responses to interactive elements), motivation (assessed by the initiative to start learning activities), and reading comprehension all evaluated against the benchmarks of personalized and student-centered learning principles within the Merdeka Belajar framework. The findings indicate that nearly all students demonstrated enthusiastic behavior and reported an increase in learning motivation. However, comprehension outcomes varied; the vast majority of the total students showed varying degrees of difficulty, indicating that visual elements alone were insufficient without an interactive glossary or guided explanations. To avoid confirmation bias, observations noted variations among students influenced by their prior digital familiarity. Several students who were less familiar with technology experienced navigation barriers and required additional support, which triggered off-task behavior in the form of confusion when operating the interactive features. Meanwhile, the teacher reported that the storybook facilitated personalized learning, but technical improvements in usability are highly required before the medium can be declared fully feasible for widespread independent use.